Time-resolved CIDNP and laser flash photolysis study of the photoreactions of N-acetyl histidine with 2,2 '-dipyridyl in aqueous solution - Tsentalovich, Y; Morozova, O; Yurkovskaya, A; Hore, P; Sagdeev, R (2000)
The reaction mechanism and details of the formation of CIDNP (chemically induced dynamic nuclear polarization) in the photoreactions of 2,2′-dipyridyl (DP) and N-acetyl histidine (HisH) in aqueous solution have been studied using laser flash photolysis and time-resolved CIDNP techniques. The triplet state TDP reacts with protonated HisH 2+ via hydrogen atom transfer with a rate constant k H = 1.2 × 10 8 M -1 s -1, and with deprotonated His - via electron transfer with k e = 7.5 × 10 9 M -1 s -1. No reaction occurs when the histidine imidazole ring is in its neutral state HisH, or when the dipyridyl triplet is protonated, TDPH +. The nuclear spin-lattice relaxation times in the radicals formed in these reactions have been determined from the CIDNP kinetics: T 1 = 44 ± 9 μs for all DP protons, T 1 = 196 ± 25 μs for the β-CH 2 protons of HisH, and T 1 = 16 ± 5 μs for the H-2 and H-4 protons of HisH. Under strongly basic conditions the CIDNP is greatly affected by degenerate electron exchange between the neutral His • radical and His - anion, with rate constant k ex = 1.5 × 10 8 M -1 S -1. © 2000 American Chemical Society.